Pemberdayaan LKSA Muhammadiyah Al-Iman Wuluhan dalam Meningkatkan Ketahanan Pangan dan Ekonomi melalui Program B2SA - Danu Indra Wardhana; Anisa Nurina Aulia; Andika Putra Setiawan; Insan Wijaya; Bejo Suroso; Afan Bagus Mananda; Fina Syafia; Alda Wata Alim Ronita; Diana Dwi Anggraeni; Ryan Setiadi Plaikol; Juvitasari (Journal of Community Development, 2026)
The availability of diverse, nutritious, balanced, and safe food (B2SA) is a fundamental need, especially for children in child welfare institutions. This community service program aimed to enhance food security and economic self-sufficiency at Muhammadiyah Al-Iman Child Welfare Institution in Wuluhan through yard utilization and aquaponic-based food processing training. The program involved 25 participants, including 2 caregivers, 3 administrators, and 20 foster children.  The activities included nutrition counseling, aquaponic cultivation training (catfish and water spinach), food processing training (catfish nuggets and water spinach sticks), and product marketing and branding management. Evaluation results showed a significant improvement in participants’ knowledge and skills, indicated by an increase in the average pre-test score from 40 to 80 in the post-test (100% improvement).  The physical outputs included three drum-based aquaponic units, packaged value-added food products with labels, and simple promotional media. The program successfully improved nutritious food availability and generated additional income opportunities. Ongoing mentoring and collaboration with local government agencies ensure sustainability. This model is effective in strengthening both food security and economic resilience and has potential for replication in similar institutions.